Intraspecies variation in the efficacy of adjunctive recombinant interferon-γ therapy against cryptococcal meningoencephalitis in mice. (9th September 2017) - Ikeda-Dantsuji, Yurika; Nakamura, Shigeki; Ohno, Hideaki; Inukai, Tatsuya; Nagi, Minoru; Ueno, Keigo; Umeyama, Takashi; Kinjo, Yuki; Yamagoe, Satoshi; Shibuya, Kazutoshi; Miyazaki, Yoshitsugu
Abstract: The efficacy of recombinant interferon γ (rIFN-γ) for cryptococcal meningoencephalitis has been poorly understood. Compared to Cryptococcus gattii, rIFN-γ significantly improved the survival in experimental meningoencephalitis due to Cryptococcus neoformans . The number of phagocytic macrophages and the levels of inflammatory cytokines production for ex vivo co-incubation with C. neoformans were increased after rIFN-γ stimulation but not C. gattii . Intraspecies differences of phagocytosis by the rIFN-γ-activated macrophages might be associated to the severity of cryptococcal infection.